Comparative transcriptome combined with biochemical and physiological analyses provide new insights toward cadmium accumulation with two contrasting Nicotiana species. Issue 1 (3rd May 2021) - Zhang, Yan; Chao, Jiangtao; Li, Xiuchun; Zhang, Chong; Khan, Rayyan; Du, Shasha; Xu, Na; Song, Lin; Liu, Haiwei; Shi, Yi
Abstract: Cadmium (Cd) is known as one of the most hazardous elements in the environment and a persistent soil constraint toxic to all flora and fauna. In this study, we conducted physiological, biochemical, and transcriptomic analyses of Nicotiana rustica ( N . rustica ) and Nicotiana tabacum ( N . tabacum ) treated with CdCl2 to know the underlying molecular mechanisms of Cd accumulation. As a result, N . rustica had more dry weight than N . tabacum . Additionally, N . rustica accumulated higher Cd concentration (69.65 times), Cd 2+ influx (1.32‐fold), glutathione S‐transferases (GST) enzyme activity (2.54 times), GSH/GSSG (oxidized form of GSH) ratio, increase of superoxide dismutase and CAT and a lower H2 O2 and superoxide (O2 − ) accumulation in their roots than N . tabacum . Cd mainly distributed in the cytoplasm of both species and N . rustica had a significant proportion in the cell wall. Furthermore, the transcriptomic analysis revealed 173 and 710 differentially expressed genes (DEGs) between control and Cd‐stressed plants in the leaves and roots of N . rustica, while 576 and 1543 DEGs were found in the leaves and roots of N . tabacum, respectively. In N . rustica, phenylpropanoid biosynthesis and phenylalanine metabolism were the most enriched pathways, while GSH metabolism, ATP‐binding cassette transporters and phenylpropanoid biosynthesis were the most enriched in N . tabacum . Finally, we found that DEGs related to metal influx, sequestration, remobilization, and chelation were responsible for Cd accumulation. These results indicated that N . rustica accumulated higher Cd content than N . tabacum, suggesting that each species utilized different response mechanism under the same Cd stress conditions. The DEGs identified in this study might lead to the identification of genes or pathways related to Cd regulation. This study identifies important regulators related to Cd accumulation.